2022
DOI: 10.3390/jcm11020469
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Ultrasound in the (peri-) Arrest Setting—A Prospective Pilot Study

Abstract: Point-of-care ultrasounds (US) are used during cardiopulmonary resuscitation (CPR) and after return of spontaneous circulation (ROSC). Carotid ultrasounds are a potential non-invasive monitoring tool for chest compressions, but their general value and feasibility during CPR are not fully determined. In this prospective observational study, we performed carotid US during conventional- and extracorporeal CPR and after ROSC with at least one transverse and coronal image, corresponding loops with and without color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several studies have used the carotid artery to compare CPR quality using POCUS. Two studies reported that sonographic blood flow measurement of the carotid artery is a non-invasive and useful method for ensuring high-quality CPR during chest compression [21,22]; however, one study reported a weak correlation between PSV and ETCO 2 values in CPR [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used the carotid artery to compare CPR quality using POCUS. Two studies reported that sonographic blood flow measurement of the carotid artery is a non-invasive and useful method for ensuring high-quality CPR during chest compression [21,22]; however, one study reported a weak correlation between PSV and ETCO 2 values in CPR [23].…”
Section: Discussionmentioning
confidence: 99%